Cadaver Study of the Diameter of the Cricoid Cartilage in Different Age Groups in A Bangladeshi Population (Mugda Medical College Journal, 2022)
Background: Accurate anatomic knowledge is essential in diagnostic and therapeutic procedures in the field of laryngology.Objective: The present study aims to determine the diameter of cricoid cartilage and demonstrate differences among different age groups in a Bangladeshi population.Materials and methods: This cross-sectional, descriptive study was done between October 2008 and March 2009. A total 60 human larynges were collected through purposive sampling from. Among them, 45 (male 23 and female 22) were collected from cadavers (9 to 60 years) at the autopsy laboratory of Department of Forensic Medicine & Toxicology, and 15 (male 6 and female 9) from stillborn infants of viable age (28 to 40 weeks of gestation) from Department of Obstetrics & Gynaecology, Mymensingh Medical College Hospital, Mymensingh, Bangladesh. The diameter of the cricoid cartilage was measured using slide calipers and the difference between age groups was determined by One-way ANOVA test.Results: The mean±SD transverse diameter of the cricoid cartilage was found as 7.40±1.72 mm ranged from 3 to 9 mm in age group A (28 to 40 weeks of gestation), 11.31±1.30 mm in age group B (9 to 16 years) ranged from 9 to 13 mm and 17.10±3.99 mm in age group C (17 to 60 years) and ranged from 10 to 24 mm. The mean transverse diameter of cricoid cartilage was highest in age group C (17.10 mm) and was lowest in age group A (7.40 mm). The difference of transverse diameter of cricoid cartilage between group A & B (P=0.001), A & C and B & C (P=0.000) were statistically significant. The mean±SD anteroposterior diameter of the cricoid cartilage was found as 10.33±1.54 mm ranged from 7 to 12 mm in age group A, 20.56±2.66 mm in age group B ranged from 15 to 25 mm and 26.79±4.37 mm in age group C and ranged from 16 to 38 mm. The mean anteroposterior diameter of cricoid was found the highest in age group C (26.79 mm) and the lowest in age group A (10.33 mm). The difference of anteroposterior diameter of cricoid cartilage between group A & B, A & C and B & C were statistically significant (P=0.000).Conclusion: Our study revealed that significant difference exists in transverse and anteroposterior diameter of the cricoid cartilage among different age groups and the values were found to increase with age.Mugda Med Coll J. 2022; 5(1): 3-7